1933
DOI: 10.1017/s0007485300031680
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Life-histories, Nutritional Requirements and Fecundity of Blowflies

Abstract: L. sericata, L. cuprina, Ch. rufifacies, C. stygia and C. augur have been bred through many generations in captivity. These flies were bred in artificial light as well as in sunlight. Inbreeding had no effect upon activity, fecundity or length of life.A diet of protein is necessary for the maturation of ova but not of spermatozoa.Oviposition is not strictly associated with a suitable larval environment, but is more in the nature of a response to a tactile stimulus. Copulation appears to provide an essential st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

1950
1950
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 6 publications
4
80
0
1
Order By: Relevance
“…Um dos aspectos que podem ter evidenciado este fato é o desgaste devido ao desenvolvimento ovariano, como também, podese sugerir que esta constatação esteja ligada a algumas características peculiares do ecossistema onde S. trivitattus ocorre. Estes resultados não corroboram com Mackerras (1933) que estudou fê-meas de várias espécies de moscas que vivem mais do que os machos. Ferraz (1992a) também obteve maior longevidade para fêmeas de P. chrysostoma e A. ingens .…”
Section: Resultsunclassified
“…Um dos aspectos que podem ter evidenciado este fato é o desgaste devido ao desenvolvimento ovariano, como também, podese sugerir que esta constatação esteja ligada a algumas características peculiares do ecossistema onde S. trivitattus ocorre. Estes resultados não corroboram com Mackerras (1933) que estudou fê-meas de várias espécies de moscas que vivem mais do que os machos. Ferraz (1992a) também obteve maior longevidade para fêmeas de P. chrysostoma e A. ingens .…”
Section: Resultsunclassified
“…Ovipositing calliphorids can produce ~200 eggs per cycle (Mackerras 1933), while larvipositing sarcophagids and calliphorids usually produce ~30-50 live larvae per cycle (Mackeras 1933;Knipling 1936). Therefore, large maggot populations may rapidly become established on carcasses.…”
Section: Introductionmentioning
confidence: 99%
“…Although the early results of Mackerras could not be substantiated in detail because of difficulties of securing successful crosses, our one fertile mating demonstrated that it was possible to obtain at least some F 1 hybrids which were apparently typical L. cuprina and also that the entire F2 progeny from some (but not all) Fl hybrids appeared to be typical L. cuprina. Mackerras (1933) found that L. cuprina characters were dominant even if the original male parent was L. cuprina and the female L. sericata, a cross which the authors could not repeat. A comparable result does not appear to have been recorded before, although it is known from mosquitoes that the characters of the female may appear in all offspring.…”
Section: Discussionmentioning
confidence: 90%
“…Successful crosses between L. cuprina and L. sericata were made ' by Mackerras (1933), but no details are· given except that a F 1 male and a F 1 female from a male L. cuprina X female L. sericata mating were both indistinguishable from typical L. cuprina. These F 1 hybrids were used in a fertility experiment, one particular female laying 3171 eggs.…”
Section: Hybridization Experimentsmentioning
confidence: 99%